Food Waste Governance Architectures in Europe: Actors, Steering Modes, and Harmonization Trends - Julia Szulecka; Carrie Bradshaw; Ludovica Principato (Global Challenges)
Abstract The scale of food waste across Europe is alarming, and its reduction is becoming an important public policy and governance issue. Sustainable Development Goal Target 12.3 constitutes a global attempt to galvanize system‐level reductions. In response, layers of varied regulation and governance at regional and national levels have emerged. This paper studies the types of governance architectures visible across Europe, what policy interventions they bring, and whether responses to the food waste challenge are converging. It looks at four leading food waste jurisdictions—France, England, Norway, and Italy—and investigates the hidden realities obscured by the simplistic division of legislative/top‐down versus voluntary/bottom‐up approaches. It applies a governance matrix to understand the variety of food waste “steering modes”, exploring both the extent to which a regime is hierarchical and/or non‐hierarchical and why. Notably, the paper also identifies some general tendencies in food waste governance, including legislative threats, challenges in distributing responsibility across the actors, focus on “low hanging fruits”, and an overall harmonization of policy responses in a neoliberal paradigm, with redistribution often pursued as a panacea for the food waste crisis.